Positional asphyxia. - S. V. Kozlov; K. N. Suloev; G. B. Aleksin; A. V. Tkachenko (Морфологія, 2016)
Background. The concept of "positional asphyxia" is considered as a separate type of mechanical asphyxia. Objective. Determination of morphological features characteristic of deaths resulting from "positional asphyxia". Results. The concept of "positional asphyxia" – a separate type of mechanical asphyxia, and the risk factors leading to death. We give expert-WIDE cases of death as a result of long-term human presence in the you-stimulated position prevents the normal respiratory movements. The analysis of morphological changes in the internal organs, arising from the death from "positional asphyxia". Conclusion. These changes in the lungs (edema and coloring) can be regarded as so-called "carmine pulmonary edema", and which is one of the types of signs of compression asphyxia from compression of the chest and abdomen. This feature developed with compression of the chest, which prevents operation of the intercostal muscles and the respiratory motion performs only the diaphragm, with a broken blood movement from the lungs into the systemic circulation and the inflow of venous blood to the lungs. As seen from the cases of "carmine pulmonary edema" may develop in terms of positional asphyxia due to similar pathophysiological factors, and it can be regarded as a specific sign of positional asphyxia.